2002
DOI: 10.1177/000348940211101104
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Suspension Laryngoscopy

Abstract: Although suspension laryngoscopy (SL) is routinely used in operative laryngology, no prospectively gathered data on the complications of this procedure have so far been available. We prospectively analyzed 339 consecutive procedures for intervention-related complications. The survey included preoperative dental status and assessment of postoperative dental, mucosal, and nerve injuries. Minor mucosal lesions were found in 75% of all patients. All healed spontaneously within a few days. Dental injuries occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
2
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 17 publications
5
91
2
5
Order By: Relevance
“…tooth extraction [11] or uvulopalatopharyngoplasty [12], MLS [4 Á6]) or even intubation, only a few studies have systematically investigated the occurrence of taste disorders after MLS [1,9,13]. With one exception [13], these studies have not measured taste function, but solely asked the patients whether they experienced taste dysfunctions [1,3,9]. Patients' subjective reports reflect the qualitative taste disorders but barely correlate with the quantitative gustatory function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tooth extraction [11] or uvulopalatopharyngoplasty [12], MLS [4 Á6]) or even intubation, only a few studies have systematically investigated the occurrence of taste disorders after MLS [1,9,13]. With one exception [13], these studies have not measured taste function, but solely asked the patients whether they experienced taste dysfunctions [1,3,9]. Patients' subjective reports reflect the qualitative taste disorders but barely correlate with the quantitative gustatory function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [1,3,9] and case reports [2,4 Á6] found transient qualitative taste disorders (dysgeusia, parageusia, metallic taste) to occur in approximately 10% of MLS patients. The authors speculated that these transient taste disorders were due to tongue compression.…”
Section: Discussionmentioning
confidence: 99%
“…The idea we had is that only the corda tympani nerve fibers were injured during the procedure. We did not find in the literature any other study investigating lingual nerve function deficit by stimulating the corda tympani nerve fibers, which are part of it, as aforementioned [4][5][6][7][8][9][10] . Taste evaluation was carried out as a means to broaden or confirm SL-related lingual nerve injury.…”
Section: Neurological Injuriesmentioning
confidence: 99%
“…1 Despite its routine use today, there are very few studies in the literature dealing with possible complications to this procedure. Most of them are restricted to doing a retrospective analysis of the complications, without any preoperative analysis 4 . Even then, literature shows that minor complications such as dental and mucosal lesions (mild bleeding, bruises, blunt or cutting wounds) happen in 9.1% to 31% of the patients who undergo direct laryngoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Les indications des laryngoscopies directes sous anesthésie générale ou laryngoscopie en suspension (LES) sont nombreuses dans un but diagnostique et/ou interventionnel (1). La LES est réalisée aux fins de diagnostic des pathologies laryngées morphologiques, neurologiques, inflammatoires et tumorales.…”
Section: Introductionunclassified